Enterprises and the environment: a necessary approach - Remy, Paul (Universidad del Pacífico, 1991)
The author deals with two issues. The first one is to explain the basis and the rationale that sustains the concerns on environment, focusing on the point that a stressed environment will limit the capacity of human kind to satisfy its needs and, with that, an absence of welfare and development. The second one is to identify aspects that closely link environment with corporations. Here, the author addresses such as corporations and poverty, the problems of cost externalities, profitability, eco business and environmental policies